Zebra Fish Lacking Adaptive Immunity Acquire an Antiviral Alert State Characterized by Upregulated Gene Expression of Apoptosis, Multigene Families, and Interferon-Related Genes - García-Valtanen, Pablo; Martínez-López, Alicia; López-Muñoz, Azucena; Bello-Perez, Melissa; Medina-Gali, Regla M.; Ortega-Villaizán, María del Mar; Varela, Monica; Figueras, Antonio; Mulero, Víctoriano; Novoa, Beatriz; Estepa, Amparo; Coll, Julio (Frontiers in Immunology, 2017)
To investigate fish innate immunity, we have conducted organ and cell immune-related transcriptomic as well as immunohistologic analysis in mutant zebrafish (Danio rerio) lacking adaptive immunity (rag1-/-) at different developmental stages (egg, larvae, and adult), before and after infection with Spring Viremia Carp Virus (SVCV). The results revealed that, compared to immunocompetent zebrafish (rag1+/+), rag1-/- acquired increased resistance to SVCV with age, correlating with elevated transcript levels of immune genes in skin/fins and lymphoid organs (head kidney and spleen). Gene sets (GS) corresponding to apoptotic functions, immune-related multi-gene families and interferon-related genes were constitutively upregulated in uninfected adult rag1-/- zebrafish. Overexpression of activated CASPASE-3 in different tissues before and after infection with SVCV further confirmed increased apoptotic function in rag1-/- zebrafish. Concurrently, staining of different tissue samples with a pan-leukocyte antibody marker, showed abundant leukocyte infiltrations in SVCV-infected rag1-/- fish, coinciding with increased transcript expression of genes related to NK-cells and macrophages, suggesting that these genes played a key role in the enhanced immune response of rag1-/- zebrafish to SVCV lethal infection. Overall, we present evidence that indicates that rag1-/- zebrafish acquire an antiviral alert state while they reach adulthood in the absence of adaptive immunity. This antiviral state was characterised by, i) a more rapid response to viral infection, which resulted in increased survival, ii) the involvement of NK-cell and macrophage-mediated transcript responses rather than B- and/or T-cell dependent cells, and iii) enhanced apoptosis, described here for the first time, as well as the similar modulation of multi-gene family/interferon-related genes previously associated to fish that survived lethal viral infections. From this and other studies, it might be concluded that some of the characteristics of mammalian trained immunity are present in lower vertebrates.